Neurodegeneration in the olfactory bulb and olfactory deficits in the Ccdc66 -/- mouse model for retinal degeneration. (December 2018) - Schreiber, Sabrina; Petrasch-Parwez, Elisabeth; Porrmann-Kelterbaum, Elke; Förster, Eckart; Epplen, Jörg T.; Gerding, Wanda M.
Highlights: CCDC66 protein is expressed throughout the early postnatal development in the WT mouse brain. CCDC66 protein expression levels in the olfactory bulb are comparable to the retina in adult (3-month-old) WT mice. The Ccdc66 -deficient retinal degeneration mouse model also exhibits impairment of the olfactory system. Severe degeneration was detected in olfactory bulb glomeruli of adult Ccdc66 -/- mice. Ccdc66 -deficient mice show alteration of olfaction-related behavior at advanced age. Abstract: The Ccdc66 -deficient ( Ccdc66 -/-) mouse model exhibits slow progressive retinal degeneration. It is unclear whether CCDC66 protein also plays a role in the wildtype (WT; Ccdc66 +/+) mouse brain and whether the lack of Ccdc66 gene expression in the Ccdc66 -/- mouse brain may result in morphological and behavioral alterations. CCDC66 protein expression in different brain regions of the adult WT mouse and in whole brain during postnatal development was quantified by SDS-PAGE and Western blot. Ccdc66 reporter gene expression was visualized by X-gal staining. Selected brain regions were further analyzed by light and electron microscopy. In order to correlate anatomical with behavioral data, an olfactory habituation/dishabituation test was performed. CCDC66 protein was expressed throughout the early postnatal development in the WT mouse brain. In adult mice, the main olfactory bulb exhibited high CCDC66 protein levels comparable to the expression in the retina. Additionally, the Ccdc66 -/- mouse brain showed robust Ccdc66 reporter gene expression especially in adult olfactory bulb glomeruli, the olfactory nerve layer and the olfactory epithelium. Degeneration was detected in the Ccdc66 -/- olfactory bulb glomeruli at advanced age. This degeneration was also reflected in behavioral alterations; compared to the WT, Ccdc66 -/- mice spent significantly less time sniffing at the initial presentation of unknown, neutral odors and barely responded to social odors. Ccdc66 -/- mice develop substantial olfactory nerve fiber degeneration and alteration of olfaction-related behavior at advanced age. Thus, the Ccdc66 -/- mouse model for retinal degeneration adds the possibility to study mechanisms of central nervous system degeneration.